Expression QTL analysis of glaucoma endophenotypes in the Norfolk Island isolate provides evidence that immune-related genes are associated with optic disc size. Issue 1 (January 2018) - Fang Kho, Pik; Lea, Rodney; Benton, Miles; Eccles, David; Haupt, Larisa; Hewitt, Alex; Sherwin, Justin; Mackey, David; Griffiths, Lyn
Abstract Primary open-angle glaucoma (POAG) is influenced by both genetic and environmental factors. Despite significant progress in identifying genetic variants associated with POAG, there remains a substantial amount of unexplained heritability. Study design features that may enhance knowledge of the genetic architecture include focusing on multiple quantitative traits related to ocular disorders (i.e. endophenotypes), targeting genetic variants that directly influence gene expression (i.e.cis -eQTLs) and utilising genetically isolated populations to reduce genetic and environmental noise and thus enhance association signals. In this study we performed heritability and blood-based eQTL association analysis of five key POAG endophenotypes in 330 individuals from the Norfolk Island (NI) isolate. Results showed evidence of heritability for all five traits, with H2 estimates ranging from 0.35 for intraocular pressure (IOP) to 0.82 for central corneal thickness (CCT) (P < 0.05). The primary finding was forBTN3A2, whereby bothcis -SNP and transcript were significantly associated with disc size within a conditional regression model. Specifically, this model included rs853676 (β = 0.23, P = 0.008) and transcript (β = 0.23, P = 0.03). We also observed acis -SNP association between optic disc size andLPCAT2 independent of transcript (P = 0.0004). These genes have specific functions in immune system pathways and suggest a role for an inherited immune component of POAG risk. This study also demonstrates an alternate approach to understanding the functional genetic basis of POAG and ocular health more generally.